2011
DOI: 10.1002/jor.21318
|View full text |Cite
|
Sign up to set email alerts
|

The role of TLE1 in synovial sarcoma

Abstract: The treatment outcome of synovial sarcoma is poor owing to its resistance to radiation and chemotherapy. The Transducin-like Enhancer of Split 1 (TLE1) is a co-repressor that involves many signaling pathways like cell survival, hematopoiesis and differentiation. Although TLE1 is uniquely expressed in synovial sarcomas, the biological role of TLE1 is not completely understood. This study evaluated the function of TLE1 in synovial sarcomas using knock-down of TLE1, and examined whether the inhibition of TLE1 sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
(28 reference statements)
1
21
0
Order By: Relevance
“…2 The inhibition of TLE1 affects not only cell proliferation but also the apoptosis pathway by suppressing Bcl-2 expression. 1 Although there is a good correlation between TLE1 expression and SS18 break-apart, their biological roles and relationship remain largely unknown. TLE1 gene is located at chromosome 9q21.32, whereas SS18 gene is at 18q11.2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The inhibition of TLE1 affects not only cell proliferation but also the apoptosis pathway by suppressing Bcl-2 expression. 1 Although there is a good correlation between TLE1 expression and SS18 break-apart, their biological roles and relationship remain largely unknown. TLE1 gene is located at chromosome 9q21.32, whereas SS18 gene is at 18q11.2.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 In several DNA microarray studies, TLE1 gene was found consistently overexpressed in synovial sarcomas. [3][4][5] By Immunohistochemistry (IHC) in formalin-fixed, paraffinembedded tissues, TLE1 expression was identified in more than 95% of synovial sarcomas, with weak or no expression in nonsynovial sarcomas, and therefore it was considered a robust diagnostic immunohistochemical marker for synovial sarcoma.…”
mentioning
confidence: 99%
“…Experimental knockdown of TLE1 in fibroblasts and synovial cells did not affect cell proliferation or enhance the cytotoxicity of chemotherapy, which suggests that TLE1 can be a good target for selectively treating synovial sarcoma without causing damage to the host tissue. However, further studies will be needed to determine a potential therapeutic role for TLE1 [32]. In the largest series of 259 cases of molecularly confirmed synovial sarcomas using a TMA, TLE1 was reported positive in 96%, but negative in others [18-20, 24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous TLE1 expression stimulated anchorage-independent growth in chicken embryo fibroblast (9). As a negative regulator of apoptosis, TLE1 inhibited low potassium-induced apoptosis in neurons (10) and protected synovial sarcoma cells from doxorubicin-mediated apoptosis (11). In line with its anti-apoptotic function, we have found that TLE1 specifically inhibited the caspase-independent cell death induced by Bit1 (Bcl2-inhibitor of transcription 1) in several types of malignant cells (12).…”
Section: Introductionmentioning
confidence: 99%